Process this : undergraduate writing in composition studies - DeJoy, Nancy C., 1958- (Utah State University Press, 2004)
In Process This, Nancy DeJoy argues that even recent revisions to composition studies, cultural studies, service learning, and social process movements--continue to repress the subjects and methodologies that should be central, especially at the level of classroom practice. Designed to move student discourses beyond the classroom, these approaches nonetheless continue to position composition students (and teachers) as mere consumers of the discipline. This means that the subjects, methodologies, and theory/practice relationships that define the field are often absent in composition classrooms. Arguing that the world inside and outside of the academy cannot be any different if the profession stays the same, DeJoy creates a pedagogy and a plan for faculty development that revisions the prewrite/write/rewrite triad to open spaces for participation and contribution to all members of first-year writing classrooms.